Alternative plant protein sources trichantera gigantea (ketum ayam) for poultry feed: A review - Muhammad Amirul Syafiq, Nasarudin; Abdul Syukor, Abd Razak; Ali Zainal-Abidin, Mohamad Termizi; Nurul Farah Anisa, Hairolnizam; Farah Amalina, Ishak; Suryati, Sulaiman; Mohd Rashid, Ab Hamid; Noraini, Samat (Penerbit UMP, 2024)
The agriculture of animals faces the difficulty of meeting the food demands of a growing global population while having limited natural resources. In recent decades, the chicken industry has made significant progress in order to meet new difficulties and changing consumer demands. The demand for an animal protein production system that considers the social, economic, and environmental dimensions of sustainability has grown. The shift away from the use of antibiotic growth promoters in animal feed has presented difficulties in preserving gut health and therefore, the performance of birds. Feed technology covers the alteration of components and the development of animal feeds, playing a crucial role in a sustainable animal production system to ensure the provision of top-notch, high-protein feed. Trichantera Gigantea (Ketum Ayam) which is high in protein content, provides ecological advantages such as soil enhancement, erosion prevention and nitrogen fixation, which can enhance crop productivity. In addition to these agricultural advantages, Trichantera Gigantea can be used as alternative plant protein sources which can reduce national’s dependency in imported protein sources thus, secured our nationals food security issues and maintains poultry health and welfare.